2007
DOI: 10.1007/s10549-007-9633-5
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and P1 polymorphisms and risk of breast cancer and fibrocystic breast conditions in Chinese women

Abstract: Enzymes encoded by the glutathione S-tranferase mu 1 (GSTM1) and pi 1 (GSTP1) genes, which are expressed in breast tissue, catalyze the detoxification of endogenous and exogenous electrophiles. Reduced enzyme activity, due to carriage of the GSTM1 deletion or the GSTP1 Ile105Val Val allele, may therefore affect susceptibility to breast cancer and related conditions. In a case-control study of Chinese women, we examined whether these polymorphisms were associated with risk of breast cancer and fibrocystic breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…Another recent Chinese study found no association of either GSTM1 null genotype or GSTP1 Ile105Val polymorphism with the risk of breast cancer. However, when the GSTM1 and GSTP1 genotypes were examined in combination, there was some suggestion of a slight increase in breast cancer risk for women carrying the GSTM1 null genotype and at least one GSTP1 Val allele [38]. These results are consistent with our findings when these two genotypes were examined in combination (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Another recent Chinese study found no association of either GSTM1 null genotype or GSTP1 Ile105Val polymorphism with the risk of breast cancer. However, when the GSTM1 and GSTP1 genotypes were examined in combination, there was some suggestion of a slight increase in breast cancer risk for women carrying the GSTM1 null genotype and at least one GSTP1 Val allele [38]. These results are consistent with our findings when these two genotypes were examined in combination (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Reding et al (2009) showed that the GSTP1 rs1695 A allele was a protective factor for BC compared with the G allele, but several other studies found no association between rs1695 and BC risk (Ramalhinho et al, 2011;Liu et al, 2013). Zhang et al (2011) reported that the minor allele homozygotes of rs1695 (GG) were associated with an increased risk of developing BC, which is consistent with three other studies in Chinese women (Chang et al, 2006;Lee et al, 2008;Sakoda et al, 2008). Liu et al (2013) found that GSTP1 rs1695 was associated with BC risk in an Asian population, but not in Caucasians or Africans.…”
Section: Discussionsupporting
confidence: 75%
“…Enzymes involved in the metabolism of steroid hormones and their metabolites, such as glutathione-S-transferases (GSTs), are of particular interest in the study of breast cancer susceptibility [5,6]. The GST superfamily belongs to the group of phase II enzymes, acting in coordination with phase I enzymes in carcinogen metabolism [5].…”
Section: Introductionmentioning
confidence: 99%